A research study on market integration of cotton (Gossypium spp.) prices in various markets of Haryana - AJAY KUMAR; S K GOYAL; VINAY KUMAR (The Indian Journal of Agricultural Sciences)
The study examined the market integration of cotton (Gossypium spp.) prices across various markets in Haryana. Monthly time series data on cotton prices were collected from 2005–06 to 2021–22 from published sources such as the Agricultural Produce Market Committees (APMC) and the Cotton Corporation of India (CCI). To analyse market integration among the selected cotton markets, various techniques were employed, including the Granger Causality test, correlation analysis, the Johansen co-integration test, and the Augmented-Dickey Fuller (ADF) test. The correlation analysis revealed a high degree of correlation among the markets, with correlation coefficients ranging from 0.97–0.99. The ADF test indicated that the level values were less than the critical value, suggesting the presence of a unit root and non-stationarity. However, at the first difference, the ADF values were greater than the critical value, indicating that the prices were stationary and no unit root was present. The Johansen co-integration analysis showed that there were no co-integrating equations at the 5% significance level based on the Maximum Eigen Statistic, while at least four co-integrating equations were identified at the 5% significance level based on the Trace statistic. Lastly, the Granger Causality test was conducted to determine the direction of causation between the price series of the selected markets in Haryana, identifying the Dabwali market as the leading cotton market.